Caring for Labuhan Merapi Tradition, One of The Local Wisdom-Based Disaster Risk Reduction Efforts - Tyas, Rizki Arumning; Pujianto, Pujianto; Suyanta, Suyanta (Komunitas, 2021)
Local wisdom is the result of the dialectic process between the individual and his environment. One of the local wisdom in Merapi Mountain, Indonesia is the traditional ceremony of Labuhan. This study is a qualitative descriptive study with literature review techniques. Based on the results of this study, it is known that the traditional ceremony of Labuhan Merapi is one of the local wisdom, tradition, culture, and traditional intelligence in the residents of the southern slope of Mount Merapi. Merapi's traditional ceremony is one of the traditional intelligence that can be managed in building a community-based disaster risk reduction system, especially at the disaster mitigation stage. Traditional intelligence is formed from the results of people's interaction with their physical environment over a long period of time. The formation of traditional intelligence allows people to know and read the signs of nature related to the eruption disaster of Mount Merapi.